Design And Implementation Synchronizing Defibrillator As Training Kit - Al-Mohtaseb, Maymoun; Al-Qawasmi, Mousa; Zeed, Yassar (جامعة بوليتكنك فلسطين - اتمتة صناعية, 2009)
Heart diseases has becom one of most common diseases in our time and as the time pass by, a major increase in people that suffer from heart diseases , like ventricular fibrillation, ventricular tachycardia, atrial flutter. So we decided in this project to design a device which treat heart diseases , this device is called defibrillator its used to apply a strong electrical shock to the heartmuscle undergoing a fatal arrhythmia the shocks can restore normal heart rhythms before the malfunctioning heart surfers sudden cardiac arrest , a seizure than can lead to death within minutes. In certain types of arrhythmia the patients ventricles maintain their ability to pump blood, as evidenced by the existence of an R wave feature in the ECCG waveform . These arrhythmias are also correctable by electrical shock to the heart, but its necessary to avoid delivering the shock during the ventricles , refractory period ( the T wave of the ECG waveform) . The shock is usually time to occur approximately 30 microsecond after the R wave peak. Human operator cannot be trusted to time the ECG waveform properly to void this problem, so the automatic electronic circuit is used A machine equipped with synchronized circuit is called a cardioverter. This device will design it into a training kit , in order to consummate advantage for students, by simplifying this device into mail parts and presentment the job of each part equally.
Keywords: Synchronizing Defibrillator